Neuroprotective effect of spiradoline and naloxone in focal cerebral ischemia: Promising behavioral and biochemical changes in Wistar rats - Binayak Deb, Ch. Sreenath, M. N. Satish Kumar, K. Elango (Journal of Applied Pharmaceutical Science)
Brain ischemia modulates endogenous opioids production and the expression of opioid receptors. The present investigations aim to determine the neuroprotective effect of Spiradoline and Naloxone, administered intraperitoneally, against carotid artery occlusion induced cerebral ischemia in adult male Wistar rats. The ischemic assessment was carried out by evaluation of behavioral (cognitive and sensorimotor), and biochemical (antioxidants, acetylcholinesterase, brain swelling and hemispheric water content) parameters. The groups included sham-operated control, vehicle control, spiradoline-treated and naloxone-treated rats. Carotid artery occlusion induced behavioral impairment as per 8-arm radial maze, elevated plus maze, sensorimotor deficits, free radical production and biochemical changes. The results revealed that spiradoline significantly (p
Keywords: Spiradoline,naloxone,occlusion,behavior,antioxidants.